(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The structural, microstructural and magnetic properties of nanoferrite NiFe2O4 (NF), CoFe2O4 (CF) and MnFe2O4 (MF) thin films have been studied. The coating solution of these ferrite films was prepared by a chemical synthesis route called sol–gel combined metallo-organic decomposition method. The solution was coated on Si substrate by spin coating and annealed at 700 °C for 3 h. X-ray diffraction pattern has been used to analyze the phase structure and lattice parameters. The scanning electron microscopy (SEM) and atomic force microscopy (AFM) have been used to show the nanostructural behavior of these ferrites. The values of average grain’s size from SEM are 44, 60 and 74 nm, and from AFM are 46, 61 and 75 nm, respectively, measured for NF, CF and MF ferrites. At room temperature, the values of saturation magnetization, Ms∼50.60, 33.52 and 5.40 emucc, and remanent magnetization, Mr∼14.33, 15.50 and 1.10 emucc, respectively, are observed for NF, CF and MF. At low temperature measurements of 10 K, the anisotropy of ferromagnetism is observed in these ferrite films. The superparamagneticparamagnetic behavior is also confirmed by χ′(T) curves of AC susceptibility by applying DC magnetizing field of 3 Oe. The temperature dependent magnetization measurements show the magnetic phase transition temperature. Nanosize ZnxNi1−xFe2O4 spinel composites with x=0, 0.2, 0.4, 0.6, 0.8 and 1 were synthesized by using surfactant (polyethylene glycol (PEG)) assisted hydrothermal route and characterized by TEM, XRD and VSM techniques. The crystallite size was calculated from different characterization methods, and magnetic core size was found to be in the range of 9–20nm from VSM.